Mechanisms of juvenile forms of ALS caused by FUS mutations - Dupuis, Luc (Henry Stewart Talks, 2023)
How do FUS mutations lead to ALS?, Is FUS also involved in FTD?, Can we therapeutically target FUS mutations?, The Dormann & Haass working model, FUS autoregulation